(untitled) (Journal of Engineering, 2020)
Tests were performed on asphalt concrete specimens with (101.6 mm in diameter and 101.6 mm in height), and the results were implemented for calculating permanent deformation and resilient modulus under repeated compressive stress with different levels of stresses (0.068, 0.138 and 0.206) MPa at 40 ºC. Two types of additives namely (carbon black-asphalt) and (SBR-asphalt) were tried as rejuvenators with three percentages of (0.5, 1 and 1.5) % by weight of asphalt cement along with two ratios of AC (1 and 2) % have been implemented as rejuvenator and blended with the reclaimed asphalt concrete. Aged materials were obtained from the site. 100% Reclaimed Asphalt Pavement material from the reclaimed mixture is implemented. A set of (3) specimens were prepared for every mixture; three specimens were tested under (repeated compressive stress) at each level of stress. The objective of this work was to study the effect of two types of additives (Styrene-Butadiene-Rubber (SBR) and carbon black) on the performance of recycled asphalt concrete mixture. It was concluded that the Resilient modulus (Mr) at (0.138 and 0.206) MPa stress level decreases by (14, 22 and 8) % and (22, 34 and 11) for reclaimed and recycle mixtures with (carbon black-asphalt and SBR-asphalt) respectively when compared with that at 0.068 MPa. Permanent deformation for recycled mixtures with (carbon black-asphalt and SBR-asphalt) increased by (65.9, 4.54) %, (146.6, 27.2) % and (79, 5.5) % at level of stresses (0.068, 0.138 and 0.206) MPa respectively when compared to reclaimed mixture.